The Effect of Two Stay-Two Stray Cooperative Learning Methods and Think Pair Share on Student Learning Outcomes of Geography - Isnain, Arif Srirahmad; Arko, Benedict (Cahaya Ilmu Cendekia Publisher, 2023)
The purpose of this study was to find out: 1) differences in student learning outcomes of Geography after using the Two Stay Two Stray, Think Pair Share and Discussion learning methods. 2) differences in Geography learning outcomes for students after using the Two Stay Two Stray and Discussion learning methods. 3) differences in student learning outcomes of Geography after using the Think Pair Share learning method with Discussion. 4) differences in student learning outcomes of Geography after using the Two Stay Two Stray and Think Pair Share learning methods in (material Distribution of Natural Disaster Prone Areas in Indonesia) class X IPS SMA Negeri 1 Sukoharjo Academic Year 2015/2016. This study uses a Quasi-Experimental research method with the design